Comprehensive assessment of host cell protein expression after extended culture and bioreactor production of CHO cell lines. Issue 8 (16th May 2022) - Hamaker, Nathaniel K.; Min, Lie; Lee, Kelvin H.
Abstract: The biomanufacturing industry is advancing toward continuous processes that will involve longer culture durations and older cell ages. These upstream trends may bring unforeseen challenges for downstream purification due to fluctuations in host cell protein (HCP) levels. To understand the extent of HCP expression instability exhibited by Chinese hamster ovary (CHO) cells over these time scales, an industry‐wide consortium collaborated to develop a study to characterize age‐dependent changes in HCP levels across 30, 60, and 90 cell doublings, representing a period of approximately 60 days. A monoclonal antibody (mAb)‐producing cell line with bulk productivity up to 3 g/L in a bioreactor was aged in parallel with its parental CHO‐K1 host. Subsequently, both cell types at each age were cultivated in an automated bioreactor system to generate harvested cell culture fluid (HCCF) for HCP analysis. More than 1500 HCPs were quantified using complementary proteomic techniques, two‐dimensional electrophoresis (2DE) and liquid chromatography coupled with tandem mass spectrometry (LC‐MS/MS). While up to 13% of proteins showed variable expression with age, more changes were observed when comparing between the two cell lines with up to 47% of HCPs differentially expressed. A small subset (50 HCPs) with age‐dependent expression were previously reported to be problematic as high‐risk and/or difficult‐to‐remove impurities; however, the vast majority of these were downregulated with age. Our findings suggest that HCP expression changes over this time scale may not be as dramatic and pose as great of a challenge to downstream processing as originally expected but that monitoring of variably expressed problematic HCPs remains critical. Abstract : In this study, Hamaker and coworkers characterized changes in CHO host cell protein profiles associated with extended cell culture. A monoclonal antibody‐producing cell line and its parental host were aged for a duration typical of a commercial seed train used to support production processes. Proteomic analysis of harvested cell culture fluid from bioreactors showed that a subset of host cell proteins exhibited variable expression, including some proteins that are known to be problematic during downstream processing steps.